A Framework for Extraterrestrial Environmental Assessment. (August 2020) - Kramer, William R.
Abstract: Many of the proposed and foreseeable activities on the Moon, Mars, and elsewhere in our solar system will require construction and similar actions. Most will, by intent, alter those natural environments in a variety of ways. Some impacts may foreclose future options for use of the area, hinder sustained access to resources, impede long-term human occupation, interfere with scientific or other purposes, harm cultural assets, create unsafe conditions, or cause other detriments. A long-proven method for reducing adverse effects here on Earth has been to assess the proposed actions in a structured manner during the planning process, to identify adverse impacts, and to seek opportunities to avoid, minimize, and mitigate harm. However, such a process is currently not required for space actions and has been largely ignored by space industries, academic and scientific organizations, and governments. In addition to advocating the need for an appropriate assessment and review process, this article proposes a simple framework as a starting point for discussion. While it draws upon environmental assessment procedures developed in the US under the National Environmental Policy Act (NEPA), it does not recommend that NEPA be applied to extraterrestrial actions. In fact, NEPA may be counterproductive. Rather, it suggests that space industries and other space actors themselves should consider developing and using an appropriately structured assessment process. Highlights: Actions on the Moon and Mars may impact those environments. A process for environmental impact assessment is needed. To date, no framework for an assessment process has been described. This article proposes an extraterrestrial environmental assessment process.